Reducing the Cost of Being the Boss: Authentic Leadership Suppresses the Effect of Role Stereotype Conflict on Antisocial Behaviors in Leaders and Entrepreneurs - Monzani, Lucas; Mateu, Guillermo; Hernandez Bark, Alina S.; Martínez Villavicencio, José (Frontiers in Psychology, 2021)
What drives entrepreneurs to engage in antisocial behaviors? Could be “invisible” forces hindering or facilitating said antisocial behaviors? Our study aims to answer these questions by applying Role Congruency Theory to the entrepreneurship arena to explain the tensions that female entrepreneurs face in the early stages of their ventures (or any who identifies with the female gender role). Our study proposes that besides the well-established female gender role – leader role incongruence, female entrepreneurs also suffer a female gender role – entrepreneur role incongruence. Indeed, we propose that all entrepreneurs (regardless of their gender) will face a leader – entrepreneur role conflict. We predicted that entrepreneurs (regardless of their gender identity) would respond to these incongruences either with a functional response (or with a dysfunctional response (embracing “in-extremis” one or two role stereotypes). We also predicted when the last occurs, the likelihood of engaging in antisocial behaviors increases. We tested our predictions in two laboratory studies. The first laboratory study tested our model in a sample of French Business school students (N = 82) and the second laboratory study in a sample of Costa Rican male and female entrepreneurs, as using male and female managers as reference groups (N = 64). Our results revealed that displaying authentic leadership reduced the likelihood of entrepreneurs (vs. managers) and men (vs. women) of engaging in antisocial behaviors such as lying to harm one’s competition or seeking an unfair advantage by cheating.